Medial rectus muscle loss: Is immediate lateral rectus disinsertion a solution? A case report with review of the literature - Bagheri, Abbas (J Curr Ophthalmol, 2018)
PURPOSE: To report a case of medial rectus (MR) muscle loss during the strabismus surgery with a late successful management and review of the literature. METHODS: The left MR was lost during resection in a 14-year-old girl who had undergone strabismus surgery elsewhere. The surgeon disinserted the antagonist lateral rectus (LR) muscle in the same session following unsuccessful attempts to retrieve the lost muscle. She was referred to our clinic two months later with a large angle exotropia and a complete lack of adduction. We performed a half-tendon transposition of vertical rectus muscles to the MR insertion and attached the residual fibers of the LR to the orbital periosteum. RESULTS: She was orthotropic after the surgery and remained stable until 6 months with a significant improvement of the adduction. CONCLUSIONS: Simultaneous LR disinsertion is not a solution for MR loss. Half-tendon transposition of the vertical recti to the original insertion of the lost MR and periosteal fixation of the LR are good options as a second-stage operation in patients with MR loss during strabismus surgery.